PENGARUH KEMAMPUAN KERJA KARYAWAN DAN KUALITAS PELAYANAN PUBLIK TERHADAP KEPUASAN PESERTA BADAN PENYELENGGARA JAMINAN SOSIAL KETENAGAKERJAAN PADA KANTOR BPJS KETENAGAKERJAAN CABANG PAPUA BARAT - Reni Ayu Shintya; Ahmad Jamil; Febry Jein Andjar; Susetyowati Sofia (Juremi: Jurnal Riset Ekonomi, 2024)
This study aims to determine the effect of employee work ability and quality public services to the satisfaction of participants of the Social Security Administering Body Employment at the Office of BPJS Employment Papua Branch. This research data obtained from questionnaires (primary data) and several observations, literature studies, and documentation. This research was conducted for 3 months, from February to May 2022. Population used in this study were participants who came to the BPJS Employment office Papua Barat Branch. The number of samples taken as many as 80 respondents. Sampling using incidental sampling technique, The data analysis technique used is Assumption Test Classical, Multiple Linear Regression Analysis, T-Test, F-Test, and Coefficient of Determination (R2). Data was collected using a questionnaire questionnaire. Based on the results of the analysis with the help of the SPSS 25 program the results of this study can be concluded as follows: results multiple linear regression analysis obtained the equation that is Y= 5,236 + 0,226 X1 + 0,440 X2 , partially each variable of employee work ability and quality of public services significant positive effect on participant satisfaction, while simultaneously employee work ability and the quality of public services have a significant positive effect to participant satisfaction. Adjusted R Square value is 0.593, which means 59.3% satisfaction participants can be explained by the employee's work ability and the quality of the rest of the public services 40.7% is explained by other variables not examined by this study